Communication Partner Training for the Primary Caregivers of People with Aphasia in India: A multi-phase exploratory study - Pais, Analisa Marie (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2022)
Aphasia, as an acquired communication disability, has an impact beyond the language impairment, affecting life participation and quality of life. Communication Partner Training (CPT) is an evidence-based intervention which aims to equip typically communicating people (from family members to healthcare workers) in the use of strategies to support communication for people with aphasia. The evidence for CPT has very limited representation from majority world countries (non-English speaking and typically low- and middle- income countries). Given that CPT aims to improve the communication between a person with aphasia and a communication partner, the sociocultural context is likely to be an important factor. This study aims to expand the evidence base on CPT to the complex and diverse socio-cultural context of India. Using a multi-phase mixed method approach, this study explores the application of CPT within one Indian state (Karnataka) by first applying ethnographic methods to the observation of two families living with aphasia. This emic perspective informed the development of a manualised, scripted intervention protocol?Communication Partner Training for the primary caregivers of people with aphasia in India (CPT-In). The impact of aphasia for 14 family dyads in which one member had aphasia, was explored using the Kagan Scales, the Kannada version of the Stroke and Aphasia Quality of Life Scale (SAQoL- K) and the adapted Sense of Coherence 13 item Scale (SOC-13); and qualitatively through an analysis of naturalistic conversations using Communication Accommodation Theory. A subset of 6 dyads then went on to participate in an exploratory multiple baseline intervention study, using a single-subject experimental design to investigate the impact of CPT-In. The combined quantitative and qualitative lenses were then used to investigate whether the CPT achieved the desired aims of (1) enhancing the use of facilitative communication strategies and (2) reducing the use of obstructive strategies during interaction. Weighted statistics were used to assess the change attributed to CPT-In on the Kagan Scales, SAQoL-K and SOC-13. Detailed qualitative analysis was applied to forty conversations, using the framework of Communication Accommodation Theory to investigate changes in communicative adjustments. The findings suggested that in both the baseline and follow up conversations, facilitative and obstructive adjustments occurred together across all dyads. Some communication partners showed an increase in instances of facilitative behaviour and decrease in instances of obstructive communicative behaviour following CPT-In. A transition was also observed in communication behaviour from a focus on the more social aspects of interaction to a focus on the meaning and interactional elements. This study acts as a strong starting point for a new era of research and development in aphasia rehabilitation within the Indian context and that of culturally similar majority world countries.
APPROVED
Keywords: Aphasia; Communication Partner Training; India; Communication Accommodation Theory; CPT